Islam: A Short History - Armstrong, Karen (London Phoenix Press, 2003)
One of the world's foremost commentators on religious affairs on the history (and destiny) of the world's most misunderstood religion.
Include Index, Maps
Keywords: Islam -- Islamic Empire